TL1A (TNFSF15) and DR3 (TNFRSF25): A Co-stimulatory System of Cytokines With Diverse Functions in Gut Mucosal Immunity - Valatas, Vassilis; Kolios, George; Bamias, Giorgos (Frontiers in Immunology, 2019)
TL1A and its functional receptor DR3 are members of the TNF/TNFR superfamilies of proteins. Binding of APC-derived TL1A to lymphocytic DR3 provides co-stimulatory signals for activated lymphocytes. DR3 signaling affects the proliferative activity of and cytokine production by effector lymphocytes, but also critically influences the development and suppressive function of regulatory T-cells. DR3 was also found to be highly expressed by innate lymphoid cells (ILCS), which respond to stimulation by TL1A. Several recent studies with transgenic and knockout mice as well as neutralizing or agonistic antibodies for these two proteins, have clearly shown that TL1A/DR3 are important mediators of several chronic immunological disorders, including Inflammatory Bowel Disease (IBD). TL1A and DR3 are abundantly localized at inflamed intestinal areas of patients with IBD and mice with experimental ileitis or colitis and actively participate in the immunological pathways that underlie mucosal homeostasis and intestinal inflammation. DR3 signaling has demonstrated a dichotomous role in mucosal immunity. On the one hand, during acute mucosal injury it exerts protective functions by ameliorating the severity of acute inflammatory responses and facilitating tissue repair. On the other hand, it critically participates in the pro-inflammatory pathways that underlie chronic inflammatory responses, such as those that take place in IBD. These effects are mediated through modulation of the relative mucosal abundance and function of Th1, Th2, Th17, Th9, and Treg lymphocytes, but also of all types of ILCs. Recently, an important role was demonstrated for TL1A/DR3 as potential mediators of intestinal fibrosis that is associated with the presence of gut inflammation. These accumulating data have raised the possibility that TL1A/DR3 pathways may represent a valid therapeutic target for chronic immunological diseases. Nevertheless, applicability of such a therapeutic approach will greatly rely on the net result of TL1A/DR3 manipulation on the various cell populations that will be affected by this approach.